2010
DOI: 10.1590/s0006-87052010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Maturação, qualidade e queda pré-colheita de maçãs 'imperial gala' em função da aplicação de aminoetoxivinilglicina

Abstract: Objetivou-se com o presente trabalho avaliar o efeito de diferentes doses e épocas de aplicação de aminoetoxivinilglicina (AVG) sobre a maturação, qualidade e queda pré-colheita de maçãs 'Imperial Gala'. O estudo foi realizado em pomar comercial localizado em Fraiburgo (SC). O delineamento experimental foi em blocos casualizados, com cinco repetições compostas de uma planta, sendo avaliados os seguintes tratamentos: 1. testemunha (sem aplicação); 2. 120 g ha-1 de AVG aplicado quatro semanas antes do ponto de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In the 2015/2016 season, the fruits that received a pre-harvest application of AVG in single or split rates had a lower SS content, followed by those subjected to the split application of AVG combined with ethephon, while the fruits of the control treatment showed higher SS values. A lower concentration of SS in 'Gala' apples sprayed with AVG was also reported by Petri et al (2010), who used a single rate of AVG, and by Hawerroth et al (2011), who applied AVG in single (120 g ha -1 30 DBAH) and split (60 g ha -1 30 DBAH + 60 g ha -1 14 DBAH) rates. The observed response may be associated with a lower starch hydrolysis in apples sprayed with AVG due to a reduction in the ethylene production rate (Brackmann et al, 2015a).…”
Section: Resultssupporting
confidence: 61%
“…In the 2015/2016 season, the fruits that received a pre-harvest application of AVG in single or split rates had a lower SS content, followed by those subjected to the split application of AVG combined with ethephon, while the fruits of the control treatment showed higher SS values. A lower concentration of SS in 'Gala' apples sprayed with AVG was also reported by Petri et al (2010), who used a single rate of AVG, and by Hawerroth et al (2011), who applied AVG in single (120 g ha -1 30 DBAH) and split (60 g ha -1 30 DBAH + 60 g ha -1 14 DBAH) rates. The observed response may be associated with a lower starch hydrolysis in apples sprayed with AVG due to a reduction in the ethylene production rate (Brackmann et al, 2015a).…”
Section: Resultssupporting
confidence: 61%
“…The solubility of cell wall components, such as pectins, was likely responsible for the high acidity observed in the NAA-treated fruit, as they are mainly composed of galacturonic acid and can increase the acidity of the juice [82] (a decrease in titratable acidity could be caused by the utilization of a high rate of oxidation for various organic acids during respiration or sugar conversion [83]). Applications of AVG or 1-MCP have been reported by previous studies to delay the synthesis of anthocyanins in the epidermis of Pink Lady [49], Imperial Gala [84], Royal Gala [34], and Brookfield [42] apples because of the delayed development of red blush and reduced skin redness. In addition, when Brookfield apples were treated with NAA, the red color index was higher, while it was lower with an NAA + AVG treatment, and this delayed the process of the development of skin color to become red [42].…”
Section: Discussionmentioning
confidence: 98%
“…This demonstrates that AVG had a negative effect on this characteristic. Other studies have also reported that AVG application delayed the synthesis of anthocyanins in the epidermis of 'Pink Lady' apples (Whale et al 2008) and 'Imperial Gala' (Petri et al 2010). AVG inhibit ethylene synthesis, which resulted in lower red skin coloration in 'Gala' apples (Amarante et al 2010;Scolaro et al 2015).…”
Section: Postharvest Quality Of 'Brookfield' Applementioning
confidence: 93%